Editorial: towards a psychophysiological approach in physical activity, exercise, and sports - Forte, Pedro (2023)
In recent years, a psychophysiological perspective on physical activity, exercise, and sports research has become more popular. Given the strong connections between psychological and physiological aspects, as well as mental fatigue and diseases, psychophysiological and psychological explanations are required. Moreover, human movement and sports performance can also be affected by psychological factors, whereby the regulation of physical capabilities is significantly influenced by the psychophysiological system. It is possible to explain how physical activity and exercise insights are controlled and managed by pacing behavior, decision-making, self-regulation, and effort perception. This Research Topic’s goal was to discuss the theoretical and methodological assumptions of the psychophysiological perspective on physical activity, exercise, and sports. In this research area, technical, tactical, physiological, cognitive, and psychological topics were explored in relation to other aspects that affect sports and exercise performance, while the effects of psychological factors on training and performance needs were evaluated. Training interventions assessing acute and chronic adaptations using evaluation and testing procedures make them one of the most important topics in this Research Topic. Research on sports coaching and its relations with mental health and performance were also welcome and considered, intending to provide recent developments within sports sciences research.